Quilombolas na Pós-Graduação construindo Ebges de resistência - deslocamentos pessoais, coletivos, político-pedagógicos e pluriepistêmicos no Ensino Superior - Silva, Andréia Rosalina (2022)
The presence of quilombolas in Brazilian postgraduate courses, from the adoption of the affirmative action policy and racial quotas, has been giving new meaning to academic knowledge, impelling new pedagogical and theoretical perspectives, especially due to their insertion and performance in communities, in projects and research groups within universities, articulating systematized scientific knowledge with their traditional knowledge. Seeking to signify this action linked to the practices of empowerment of writing, of the processes of construction of knowledge and identities, this thesis aims - taking for analysis the context of four Brazilian public universities (namely: Universidade de Brasília, Universidade Federal de Goiás , Universidade Federal do Recôncavo Baiano and Universidade Federal da Bahia) – to evaluate the impact of access to graduate studies for quilombolas in terms of quotas, analyzing their personal transformations, in their community and within the academy (institutional). Our study starts from a historical-socio-anthropological reading about the struggle of Afro-Brazilian communities in Brazil, in search of access to education, in the context of the 1988 Constitution, the Racial Equality Statute, Decree 4.887/2003, Article 68 of the ADCT, of the Opinion CNE/CEB 16/2012 and of the Resolution 08/2012 of the National Council of Education (CNE) until the normative ordinance of the MEC nº 13, of May of 2016, having the hypothesis that such subjects, when inserted in the higher education, in postgraduate studies, reformulate the formal educational process, decolonize the curricula and bring visibility to their experiences and pedagogical practices.